Trends and projections of overweight and obesity among Chinese college students from 1995 to 2019: Findings from national cross-sectional surveys - Pengying Du; Jianhua Zhang; Ling Zhang (PLoS ONE, 2026)
Background This paper aimed to investigate the prevalence of overweight and obesity among Chinese college students aged 19–22 years from 1995 to 2019 and projections to 2030. Methods Data among 291,276 Han Chinese college students aged 19–22 years were obtained from the Chinese National Surveillance on Students’ Constitution and Health from 1995 to 2019. Weight categories were based on standardized weight-for-height values by sex and age. The chi-square trend test was used to estimate trends in prevalence across subgroups. Log-binomial regression was used to estimate the prevalence odds ratios. Results The prevalence of overweight and obesity among college students aged 19–22 years progressively increased from 3.7% and 0.7% in 1995 to 23.4% and 11.4%, respectively, in 2019 ( P < 0.001). Significant increasing trends were observed in all the subgroups ( P < 0.001). The increases in the prevalence of overweight and obesity accelerated. The risk of overweight (prevalence odds ratios (PORs): 1.42 ~ 3.01, P < 0.001) and obesity (PORs: 2.82 ~ 4.42, P < 0.001) was greater for males from 1995 to 2019 and for urban students (overweight: 1.21 ~ 1.63, P < 0.001; obesity: 1.31 ~ 1.97, P = 0.004~<0.001) from 2000 to 2019. The risk was lower for urban students in 1995 than for rural students. In recent years, older college students have been at greater risk. Based on our findings, we expect that the prevalence of overweight and obesity in all subgroups will continue to increase from 2025 to 2030. The prevalence of overweight among rural college students can be predicted to exceed that among urban college students after 2027. Conclusion The prevalence of overweight and obesity among Chinese college students increased from 1995 to 2019. Future policies should focus on high-risk groups, especially rural and male students, to improve the health and equity of college students.